All-in-one: a versatile gas sensor based on fiber enhanced Raman spectroscopy for monitoring postharvest fruit conservation and ripening. Issue 6 (17th February 2016) - Jochum, Tobias; Rahal, Leila; Suckert, Renè J.; Popp, Jürgen; Frosch, Torsten
Abstract : A single FERS sensor for simultaneous oxygen (O2 ), carbon dioxide (CO2 ), ammonia (NH3 ), and ethylene (C2 H4 ) monitoring is presented for applications in postharvest fruit management. Abstract : In today's fruit conservation rooms the ripening of harvested fruit is delayed by precise management of the interior oxygen (O2 ) and carbon dioxide (CO2 ) levels. Ethylene (C2 H4 ), a natural plant hormone, is commonly used to trigger fruit ripening shortly before entering the market. Monitoring of these critical process gases, also of the increasingly favored cooling agent ammonia (NH3 ), is a crucial task in modern postharvest fruit management. The goal of this work was to develop and characterize a gas sensor setup based on fiber enhanced Raman spectroscopy for fast (time resolution of a few minutes) and non-destructive process gas monitoring throughout the complete postharvest production chain encompassing storage and transport in fruit conservation chambers as well as commercial fruit ripening in industrial ripening rooms. Exploiting a micro-structured hollow-core photonic crystal fiber for analyte gas confinement and sensitivity enhancement, the sensor features simultaneous quantification of O2, CO2, NH3 and C2 H4 without cross-sensitivity in just one single measurement. Laboratory measurements of typical fruit conservation gas mixtures showed that the sensor is capable of quantifying O2 and CO2 concentration levels with accuracy of 3% or less with respect to reference concentrations. The sensor detected ammonia concentrations, relevant for chemical alarm purposes. Due to the high spectral resolution of the gas sensor, ethylene could be quantified simultaneously with O2 and CO2 in a multi-component mixture. These results indicate that fiber enhanced Raman sensors have a potential to become universally usable on-site gas sensors for controlled atmosphere applications in postharvest fruit management.